2019
DOI: 10.1093/mnras/stz553
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopy of the candidate AGNs in Henize 2–10 and NGC 4178: likely supernova remnants

Abstract: Black holes in dwarf/bulgeless galaxies play a crucial role in studying the co-evolution of galaxies and their central black holes. Identifying massive black holes in dwarf galaxies suggests that the growth of black holes could precede that of galaxies. However, some of the most intriguing candidate active galactic nuclei (AGN) in small galaxies have such low luminosities that the sample is vulnerable to contamination by other sources, such as supernova remnants. We re-analysed Chandra X-ray Observatory observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…However, Cresci et al (2017) found that the optical emission line diagnostics at the centre of He2-10 was fully consistent with star formation and showed that the X-ray luminosity found previously was consistent with emission from supernovae. Finally, Hebbar et al (2019) have recently found that SN models of X-ray emission explain much better the observed X-ray spectrum of He2-10 than an AGN power law.…”
Section: Figure B1mentioning
confidence: 98%
“…However, Cresci et al (2017) found that the optical emission line diagnostics at the centre of He2-10 was fully consistent with star formation and showed that the X-ray luminosity found previously was consistent with emission from supernovae. Finally, Hebbar et al (2019) have recently found that SN models of X-ray emission explain much better the observed X-ray spectrum of He2-10 than an AGN power law.…”
Section: Figure B1mentioning
confidence: 98%
“…Several of the AGN candidates in late-type galaxies originally identified through detection of [O IV] 25.89 µm or [Ne V] 14.32 µm have since been followed up in X-rays (Gliozzi et al 2009, McAlpine et al 2011, Georgakakis et al 2011, Secrest et al 2012, Hebbar et al 2019, and in general the X-rays are found to be weaker than expected. Diffuse, thermal emission is occasionally detected when the data are of sufficient quality.…”
Section: Multi-wavelength Searches and Confusion With Star Formationmentioning
confidence: 99%
“…Higher-resolution data revealed multiple components to the central X-ray source, moving the fundamental plane mass estimate up to log M/M ∼ 7 . Subsequent work showed that the X-ray spectrum of the nuclear source is more consistent with a supernova remnant than an AGN (Hebbar et al 2019), although the possible presence of hour-scale variability would not favor this scenario , Hebbar et al 2019. There is also no evidence for AGN ionization in the galaxy center (Cresci et al 2017).…”
Section: Going Further With the Fundamental Plane Of Radio Activitymentioning
confidence: 99%
“…First, we used the Akaike Information Criterion values (Akaike 1974), as done by Hebbar et al (2019). These values are defined as 4 :…”
Section: Evaluating the Significance Of The Ufo Componentsmentioning
confidence: 99%